IMPLEMENTASI AKAD MURABAHAH BERBASIS MARGIN PADA MASA PANDEMI COVID-19 - Zulvia, Awin Rahma; Nawirah, Nawirah (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Researchers choose the research objects in BRI Syariah Malang Branch because they have high customer trust. Financing products at BRI Syariah Malang Branch one of them is murabahah. Murabahah is a product to buy and sell financing in cash and credit in accordance with Islamic principles. This study aims to find out the effect of the covid-19 pandemic on the use of murabahah margins. This research uses qualitative methods with two approaches, namely interviews and in-depth observations. The results of this study confirm that murabahah financing is the most desirable financing in the pandemic period of 93.2% and the most effective murabahah margin used during pandemics is the annuity method. The determination of this margin is in accordance with DSN Fatwa No: 84/DSN-MUI/XII/2012 on the determination of Murabahah Financing Benefits.